Diabetes as a risk factor for stroke in women compared with men: A systematic review and meta-analysis of 64 cohorts, including 775 385 individuals and 12 539 strokes - Peters, S.; Huxley, Rachel; Woodward, M. (2014)
Background Diabetes mellitus is a major cause of death and disability worldwide and is a strong risk factor for stroke. Whether and to what extent the excess risk of stroke conferred by diabetes differs between the sexes is unknown. We did a systematic review and meta-analysis to estimate the relative effect of diabetes on stroke risk in women compared with men. Methods We systematically searched PubMed for reports of prospective, population-based cohort studies published between Jan 1, 1966, and Dec 16, 2013. Studies were selected if they reported sex-specific estimates of the relative risk (RR) for stroke associated with diabetes, and its associated variability. We pooled the sex-specific RRs and their ratio comparing women with men using random-effects meta-analysis with inverse-variance weighting. Findings Data from 64 cohort studies, representing 775 385 individuals and 12 539 fatal and non-fatal strokes, were included in the analysis. The pooled maximum-adjusted RR of stroke associated with diabetes was 2·28 (95% CI 1·93-2·69) in women and 1·83 (1·60-2·08) in men. Compared with men with diabetes, women with diabetes therefore had a greater risk of stroke-the pooled ratio of RRs was 1·27 (1·10-1·46; I2=0%), with no evidence of publication bias. This sex differential was seen consistently across major predefined stroke, participant, and study subtypes. Interpretation The excess risk of stroke associated with diabetes is significantly higher in women than men, independent of sex differences in other major cardiovascular risk factors. These data add to the existing evidence that men and women experience diabetes-related diseases differently and suggest the need for further work to clarify the biological, behavioural, or social mechanisms involved.